Global Research Trends on Ablation for Hepatocellular Carcinoma: Insights from A Comprehensive Bibliometric Analysis and Visualization - Athoillah, Nabil; Hibatullah, Muhammad Naufal; Buaji, Brilliantara; Rayyan, Muhammad Isra; Febriakhano, Aji (Indonesian Journal of Cancer, 2026)
Background: Ablation has been intensively studied as an effective and minimally invasive management for hepatocellular carcinoma (HCC). Plenty of publications have been written in the last century about ablation in HCC, but no bibliometric analysis has comprehensively analyzed the topic of ablation in HCC. This study aimed to explore the recent development of HCC ablation using bibliometric analysis. Methods: Publication data were comprehensively retrieved from the Scopus database using total sampling technique from the first publication to August 3, 2024. Then, the data were analyzed and visualized using VOSviewer and RStudio software to reveal publications per year, most frequently occurring keywords, most productive authors and countries, article citations, and international collaborations.Results: Thirteen thousand, nine hundred fifty-five publications were extracted from the Scopus database between 1950 and 2024. The research trend on ablation and HCC has increased massively, especially since 1999. China and the World Journal of Hepatology were identified as the most productive countries and journals in this field. In addition, Kudo Masatoshi has 187 articles and is the most influential researcher in this field. The bibliometric data illustrated that the most frequently reviewed ablation modality was radiofrequency ablation, followed by microwave ablation, percutaneous ethanol injection, and high-intensity focused ultrasound. In addition, the bibliometric analysis showed that recent ablation research trends favored microwave ablation and high-intensity focused ultrasound as ablation techniques, using efficacy and safety parameters as primary outcomes. Meta-analysis is a research method related to ablation that has primarily been conducted recently. Ablation modalities are also frequently studied simultaneously with immunotherapy, systemic, and locoregional modalities.Conclusions: Current research on HCC ablation continues to increase, with study trends shifting from percutaneous ethanol injection and radiofrequency ablation to microwave ablation and high-intensity focused ultrasound. Meta-analysis and efficacy-safety are essential research methods and outcomes to review.